2019
DOI: 10.1371/journal.pone.0212038
|View full text |Cite
|
Sign up to set email alerts
|

Investigating pathways linking women’s status and empowerment to skilled attendance at birth in Tanzania: A structural equation modeling approach

Abstract: Maternal and newborn mortality remain unacceptably high in sub-Saharan Africa where use of a skilled birth attendant (SBA) at delivery has remained low. Despite the recognized importance of women’s empowerment as a key determinant of maternal and newborn health, evidence from sub-Saharan Africa is more limited. Using data from the 2010 Tanzania Demographic and Health Survey (n = 4,340), this study employs a robust method–structural equation modeling (SEM)–to investigate the complex and multidimensional pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 41 publications
6
15
0
Order By: Relevance
“…Among the three variables in socio-cultural empowerment, educational attainment was found to be influential in both urban and rural areas as higher educated women reported greater odds of using SBAs. Similar results were reported in other studies in Nepal [ 11 , 34 ] and elsewhere [ 7 , 12 , 35 – 39 ]. A possible reason might be that lower educated women lack awareness and tend to follow traditional delivery methods.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among the three variables in socio-cultural empowerment, educational attainment was found to be influential in both urban and rural areas as higher educated women reported greater odds of using SBAs. Similar results were reported in other studies in Nepal [ 11 , 34 ] and elsewhere [ 7 , 12 , 35 – 39 ]. A possible reason might be that lower educated women lack awareness and tend to follow traditional delivery methods.…”
Section: Discussionsupporting
confidence: 92%
“…Decision making was not influential in both urban and rural areas in this study, which is consistent with the result of a study conducted in Senegal [18]. However, women's decision making power was significantly associated with using SBAs in other studies in Nepal [16] and elsewhere [6,8,11,12,19,22,24,[48][49][50]. We did not analyze three aspects (health decisions, movement and larger household purchases) of decision making separately and whether each aspect may have a different effect; rather, we combined them into one variable with two levels.…”
Section: Familial/interpersonal Empowermentsupporting
confidence: 90%
See 1 more Smart Citation
“…Some African women often have limited autonomy and control over their health. Autonomy and decision making power facilitate the use of health services [12], [13], [16]- [19], [22]- [24]. Studies conducted in Ethiopia [16], Tanzania [22] and Nigeria [17] found a strong association of community-level women's autonomy and maternal healthcare service utilization while others found a weak relationship [23].…”
Section: Gender Social and Cultural Valuesmentioning
confidence: 99%
“…Autonomy and decision making power facilitate the use of health services [12], [13], [16]- [19], [22]- [24]. Studies conducted in Ethiopia [16], Tanzania [22] and Nigeria [17] found a strong association of community-level women's autonomy and maternal healthcare service utilization while others found a weak relationship [23]. On the other hand, lack of power to make decisions [25], no one to assist at the onset of labor at night [18], heavy workloads especially in the rainy season [18], [19], gender-based violence, lack of women empowerment [18], [19], lack of spousal support, lack of support from family and community, require permission from husband or family [19], [21] and health workers' attitudes towards women [12] are gender-related barriers identified in the review.…”
Section: Gender Social and Cultural Valuesmentioning
confidence: 99%